Profil Literasi Sains Siswa Sekolah Dasar Pada Pembelajaran Ilmu Pengetahuan Alam dan Sosial - Bukhari, Hasbullah Bin; Prayogi, Saiful; Muhali, Muhali (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aims to analyze the science literacy profile of primary school students in learning Natural and Social Sciences. The study used a quantitative descriptive approach with 31 students as samples. The results showed that students’ science literacy was in the very low to low category, especially in the aspects of procedural, epistemic, scientific competence and content knowledge. Inquiry-based learning is still limited and the lack of integration of local contexts in learning. The development of local wisdom-based teaching materials is needed to improve student understanding and engagement. This research recommends teacher training and community collaboration to utilize local cultural elements as a context for science learning. The findings make an important contribution in designing relevant innovative learning strategies to significantly improve students’ science literacy.